Kajian Kehilangan Hasil pada Pengeringan dan Penggilingan Padi di Lahan Pasang Surut Sumatera Selatan - Budi Raharjo; Dedeh Hadiyanti; Kgs. A. Kodir (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Raharjo et al., 2000.Â Study of Yield Losses during Drying and Milling of Paddy in Tidal Lowland of South Sumatra. J. Lahan Suboptimal 1(1):72-82.In tidal lowland of South Sumatra low quality rice called beras batik is commonly found. Beras batik is rice that is low in both quality and prices. The low quality rice grains have high fracture, the percentage of head rice is only 25%, while the percentage of yellow grain exceeds 50%, and its selling price is only Rp. 1800/kg in 2004. The main causes were poor harvest and post harvest handling, delaying harvest and post harvest due to the lack of manpower and facilities owned by farmers. The condition was worsened by the heavy rainfall during harvest time and sometimes coincided with high tide. The study was conducted on July 2011 (dry season) in tidal lowland reclamation area of Telang Rejo village, Muara Telang Sub-district, Banyuasin Regency. In this study 2 post-harvest technologies were introduced to improve harvesting techniques and post harvest handling; (1) Drying assessment of Grain Dryer Machine Fueled withhusk, and (2) Study the Different Configurations of Rice Milling Unit. Lost during drying was 2.77 for sun drying compared to 7.13% with box dryer. Field testing at RMU 1 showed that milling recovery using box dryer (63.5%) was higher than sun drying (61.6%). But, at RMU 2 milling recovery for box dryer (61.3%) was lower than sun drying (63.7%). For milling losses, box dryer (4.99%) was lower than sun drying (5.99%).